What's an Ark? - Payne, Mark (Relegere, 2018)
An organism threatened with extinction is entrusted to safe storage in the hope that the conditions it needs to survive might one day be available to it again. The ark of Genesis has been widely used to imagine conservation projects of this kind. My paper circumscribes ark building as a conservation activity with other instances of ark building in contemporary culture, from Lars von Trier’s Melancholia to Lee Scratch Perry’s Black Ark. What is at stake when we decide that some form of life is, or is not, worthy of being set on its way to a life to come?